The access to complementary and integrative health practices in public health system in Brazil. (30th September 2020) - Magalhaes, F; Santos, D; Martins, G; Barbosa, J; Riquieri, M; Cordeiro, M; Silva, M; Lima, R; Sarti, T; Andrade, M
Abstract: Background: A qualitative and exploratory study that analyzed the perspective of access to Integrative and Complementary Practices in Health (PICS) by listening users from a selected service of primary care of a municipality. Objective: Analyze the access to PICS in a health public service of a municipality in a state of Brazil, from the perspective of users, as well as aimed at understand the needs and desires of health care these users in the search process and use of PICS, identifying facilitators and barriers in this trajectory. Methods: The theoretical reference from Frenk on access was used, which systematizes the flow of events at the moment when the health need is perceived until the effectiveness of the care, besides the demand and entrance in the health services and the continuity of the treatment. The data collection was done by participant observation and semi-structured interview with 29 users of the service. The narratives were worked through the analysis of thematic content. Results: The results indicated two groups of PICS: complex medical systems and therapeutic resources. There were differences in the organization of the offer with consequent influence on the different forms of access. It was registered the interest for the use of health care in a non-biomedical logic and a re-signification of the health-disease process in PICS users, contributing to the continuity of health production. Conclusions: It was concluded that the current models of access analysis do not contemplate the diversities of access to the PICS, and the various possibilities of encounters with these practices allow the identification of the marginality of this care in all cases analyzed. Key messages: Integrative and Complementary Health Practices gain national relevance as they contribute to the development of health promoting activities, focus on the individual, prevention and comprehensive care. However, considered a controversial topic in a hegemonically biomedical scenario, the incorporation of these new knowledge and practices in the health field occurs in a marginal way.